SOIL AND WATER ANALYSIS FOR MICRO-NUTRIENTS IN WETLAND’S ASSOCIATED GRASSLAND ECOSYSTEMS - S. T. Raza; Z. Ali; I. Zainab; S. Sidra; A. Nimra; Z. Zona; K. Aziz (Journal of Animal and Plant Sciences, 2015)
Soil and water degradation put crucial impact on the global ecosystems and human health. The paper focuses on the principal chemical and physical attributes serving as indicator of soil and water quality of the grassland and wetland of Makra Meadows (Elevation 3089 m) and Kallar Kahar, (Elevation 554 m) Pakistan. Soil samples were collected from the topsoil, at a depth of 30 cm and 60 cm from both locations while water samples were collected from the natural lakes present in both ecosystems. Practiced indicators considered in soil analysis at three different depths and gradients of soil embrace EC, pH, organic matter, phosphorus, potassium, and texture and percentage saturation while the water quality assessment comprised of electrical conductivity, Ca++ and Mg++, Na+, Cl-, carbonates, and bicarbonates. Soil and water data is presented to provide necessary information about natural ecosystems.
Keywords: Soil & water quality; Ecosystem; Makra meadows; Kallar Kahar; Pakistan